Pengaruh Substitusi Terigu dengan Tepung Komposit Tapioka dan Glukomanan-Karaginan Terhadap Kadar Serat Kasar dan Sifat Sensori Mie Basah - Godras Jati Manuhara; Setyaningrum Ariviani; Dwi Ishartani (Caraka Tani: Journal of Sustainable Agriculture, 2007)
Composite fluor was made from combination of tapiocca and glucomannan-carrageenan in four different composition. The composite fluor for wheat in producing wet noodle. Amylose content of tapiocca provide strong structure of wet noodle, while combination of carrageenan-glucomannan objected to substitute gluten function in building elastic bonding needed in the wet noodle. Increasing of the composite fluor level increased raaw fiber content of wet noodle. Based on sensory analysis, substitution of wheat by the composite fluor decreased intensity of brightness, hardness, unique taste and aroma of wet noodle, but in the other side, retained its elasticity at two level of substitution (18% tapiocca mixed with 2% carrageenan-glucomannan and 19% tapiocca mixed 1% carrageenan-glucomannan).